THE EARLY DYNASTIC MONUMENTAL BUILDINGS AT UMM AL-AQARIB1. (17th March 2015) - Oraibi Almamori, Haider
Abstract : This article presents the results of excavations conducted at the site of Umm al-Aqarib, in the Dhi Qar Governorate of Iraq, in the years 1999–2002 and 2008–2010. Despite significant practical difficulties, the excavations revealed an Early Dynastic city of major importance, with monumental architecture including two large temples, called here the White Temple and Temple H, and a palace. In interpreting the excavation results, the author argues that Umm al-Aqarib, and not Jokha (Umma) as has previously been thought, was the central settlement of the kingdom of Gišša during the Early Dynastic III period, and that the White Temple, the largest yet known from Early Dynastic Sumer, is to be identified as the temple of Šara, city god of Gišša.